The role of positive and negative brand engagement on affective commitment and self-expression word-of-mouth, using extraversion as a moderator: the brand communities context - Marques, Maria Inês Lameiras (2017)
The main goal of this dissertation is to examine that consumer-brand engagement is not exclusively related to positive processes or interactions between the involved entities. Thus, it tries to demonstrate that individuals who dislike, claim to hate, or develop unfavourable feelings toward the brand, can also be engaged with it and, specifically, with the community he/she is part of. The study also explores the influence of extroversion as moderator in the relationship between brand engagement and affective commitment and between brand engagement and selexpression word-of-mouth. To illustrate these ideas, using a sample of 700 individuals, worldwide, it was possible to collect data from 8 sources: one fan and one anti-brand community of Sporting Clube de Portugal, one fan and one anti-brand community of McDonald’s, one fan and one anti-brand community of Starbucks, and one fan and one antibrand community of Apple Inc. The findings from this research illustrate that communities have different motivations for engaging with the community and the brand online, and that they influence, to some extent, some communities’ affective commitment and self-expression WOM, even with the moderation of extraversion. The findings also provide support for the key arguments proposed and open paths for further exploration of the concept of negative engagement and, specifically, negative online brand engagement – upcoming and fundamental areas of research in the Marketing. Further implications for managers, and future research paths are discussed.